Cognitively Inspired Audiovisual Speech Filtering Towards an Intelligent, Fuzzy Based, Multimodal, Two-Stage Speech Enhancement System / by Andrew Abel, Amir Hussain. - Abel, Andrew. (SpringerBriefs in Cognitive Computation, 2015)
.